2014
DOI: 10.1177/1524838014557286
|View full text |Cite
|
Sign up to set email alerts
|

Social Information Processing Mechanisms and Victimization

Abstract: The aim of the current literature review, which is based on 64 empirical studies, was to assess to what extent mechanisms of the Social Information Processing (SIP) model of Crick and Dodge (1994) are related to victimization. The reviewed studies have provided support for the relation between victimization and several social information processing mechanisms, especially the interpretation of cues and self-efficacy (as part of the response decision). The relationship between victimization and other mechanisms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 100 publications
(162 reference statements)
1
27
1
Order By: Relevance
“…This particular group might have difficulties in processing information related to bullying experience because: (1) peer nomination has been considered as a “gold standard” for the assessment of bullying experience (Graham & Juvonen, ; Ladd & Kochenderfer‐Ladd, ; Österman et al, ; Verlinden et al, ); and (2) self‐report of bullying experience depends on one's ability to interpret and reconstruct social events, and their willingness to report painful experience (Graham & Juvonen, ; Ladd & Kochenderfer‐Ladd, ;; Vessey et al, ). Previous studies also have demonstrated impairment of social information processing in victims and perpetrators of bullying, either by self‐report (Laible et al, ; Ziv et al, ) or parent/peer report (van Reemst, Fischer, & Zwirs, ; Ziv, ). When presented with an ambiguous social scenario, children, and adolescents who report bullying experience tend to interpret these situations as hostile, with higher levels of aggression, anger, and retaliation than do children without bullying experiences (Camodeca & Goossens, ; Hubbars et al, ; Lansford, Malone, Dodge, Pettit, & Bates, ; Lemerise & Arsenio, ; Pellegrini, Bartini, & Brooks, ; van Reemst et al, ; Ziv et al, ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This particular group might have difficulties in processing information related to bullying experience because: (1) peer nomination has been considered as a “gold standard” for the assessment of bullying experience (Graham & Juvonen, ; Ladd & Kochenderfer‐Ladd, ; Österman et al, ; Verlinden et al, ); and (2) self‐report of bullying experience depends on one's ability to interpret and reconstruct social events, and their willingness to report painful experience (Graham & Juvonen, ; Ladd & Kochenderfer‐Ladd, ;; Vessey et al, ). Previous studies also have demonstrated impairment of social information processing in victims and perpetrators of bullying, either by self‐report (Laible et al, ; Ziv et al, ) or parent/peer report (van Reemst, Fischer, & Zwirs, ; Ziv, ). When presented with an ambiguous social scenario, children, and adolescents who report bullying experience tend to interpret these situations as hostile, with higher levels of aggression, anger, and retaliation than do children without bullying experiences (Camodeca & Goossens, ; Hubbars et al, ; Lansford, Malone, Dodge, Pettit, & Bates, ; Lemerise & Arsenio, ; Pellegrini, Bartini, & Brooks, ; van Reemst et al, ; Ziv et al, ).…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies also have demonstrated impairment of social information processing in victims and perpetrators of bullying, either by self‐report (Laible et al, ; Ziv et al, ) or parent/peer report (van Reemst, Fischer, & Zwirs, ; Ziv, ). When presented with an ambiguous social scenario, children, and adolescents who report bullying experience tend to interpret these situations as hostile, with higher levels of aggression, anger, and retaliation than do children without bullying experiences (Camodeca & Goossens, ; Hubbars et al, ; Lansford, Malone, Dodge, Pettit, & Bates, ; Lemerise & Arsenio, ; Pellegrini, Bartini, & Brooks, ; van Reemst et al, ; Ziv et al, ). Findings from our study add support to these previous results that adolescents who might misinterpret neutral or ambiguous situations as bullying, are also showing later increased externalizing, as well as internalizing behavior.…”
Section: Discussionmentioning
confidence: 96%
“…80 Studies in other populations also found these interpretations, referred to as hostile attributions of the situation, to be related to victimisation: people who interpret hypothetical situations as more hostile, generally, also experience more victimisation. 81 Aquino, Douglas and Martinko 82 have found a relationship between workplace violence and various other negative attributions, namely the tendency to attribute negative outcomes as external to themselves, stable, intentional and controllable. Studying hostile attributions as a possible indicator of workplace violence could thus be worthwhile.…”
Section: Psychological Characteristics and Behaviour Of Professionalsmentioning
confidence: 99%
“…To date, the response decision and emotions have predominantly been used successfully to explain aggressive behaviour (for example, Kempes et al, 2005). Moreover, in several recent studies, the SIP dimensions and emotions have also been found to be related to victimization (Van Reemst et al, 2014). Because studies on response decision, emotions, and the victimization of police officers are limited, we have based our expectations on victimization studies in other populations.…”
Section: Hypothesizing the Relationship With Victimization Of Police mentioning
confidence: 99%